Cytochrome P450-type Hydroxylation and Epoxidation in a Tyrosine-liganded Hemoprotein, Catalase-related Allene Oxide Synthase - Boeglin, William E. (American Society for Biochemistry and Molecular Biology, 2012)
The ability of hemoproteins to catalyze epoxidation or hydroxylation reactions is usually associated with a cysteine as the proximal ligand to the heme, as in cytochrome P450 or nitric oxide synthase. Catalase-related allene oxide synthase (cAOS) from the coral Plexaura homomalla, like catalase itself, has tyrosine as the proximal heme ligand. Its natural reaction is to convert 8R-hydroperoxy-eicosatetraenoic acid (8R-HPETE) to an allene epoxide, a reaction activated by the ferric heme, forming product via the Fe(IV)–OH intermediate, Compound II. Here we oxidized cAOS to Compound I (Fe(V)=O) using the oxygen donor iodosylbenzene and investigated the catalytic competence of the enzyme. 8R-hydroxyeicosatetraenoic acid (8R-HETE), the hydroxy analog of the natural substrate, normally unreactive with cAOS, was thereby epoxidized stereospecifically on the 9,10 double bond to form 8R-hydroxy-9R,10R-trans-epoxy-eicosa-5Z,11Z,14Z-trienoic acid as the predominant product; the turnover was 1/s using 100 μm iodosylbenzene. The enantiomer, 8S-HETE, was epoxidized stereospecifically, although with less regiospecificity, and was hydroxylated on the 13- and 16-carbons. Arachidonic acid was converted to two major products, 8R-HETE and 8R,9S-eicosatrienoic acid (8R,9S-EET), plus other chiral monoepoxides and bis-allylic 10S-HETE. Linoleic acid was epoxidized, whereas stearic acid was not metabolized. We conclude that when cAOS is charged with an oxygen donor, it can act as a stereospecific monooxygenase. Our results indicate that in the tyrosine-liganded cAOS, a catalase-related hemoprotein in which a polyunsaturated fatty acid can enter the active site, the enzyme has the potential to mimic the activities of typical P450 epoxygenases and some capabilities of P450 hydroxylases.